DESA TANGGUH BENCANA DALAM UPAYA PENINGKATAN KONDISI SOSIAL EKONOMI PASCA GEMPA BUMI MASYARAKAT DESA PANSOR, KEC. KAYANGAN, KAB. LOMBOK BARAT, NUSA TENGGARA BARAT - Sugian, Ahmad; Natsir, Abdul; Pranadi, Agung; Saputri, Ardita Juliana; Sundusiah, Baiq; Faldiansah; Katrina; Setiawan, Micko Yusuf; Yunita, Nanda; Purnamawati; Ranaseptiani, Silfa (Jurnal Wicara, 2024)
Indonesia is one of the countries prone to natural disasters, one of which is an earthquake that causes impacts caused by the disaster event in the form of losing jobs, homes, and even beloved family members. An earthquake disaster occurred in 2018 in Lombok and was centered in North Lombok Regency, one of the affected areas was Pansor Village both from social and economic aspects. The earthquake caused various kinds of losses such as property losses, socio-economic, environmental damage, loss of human life and so on, so in this case Pansor Village was used as an object of study in community service. The implementation of the program follows the schedule set by LPPM University of Mataram. Activities are focused on program implementation that focuses on communication and observation methods such as the socialization of earthquake disaster mitigation which aims to provide information and knowledge of the importance of always being prepared for the arrival of earthquake disasters. early marriage socialization aims to provide direction on the dangers of early marriage and conduct banana processing workshops so that they are of high selling value which aims to develop raw materials into high-value production materials. With these activities, it is expected that the community will be able to develop raw materials into production materials. Implementation of the community empowerment program is carried out by providing counseling and training. Counseling is given using the lecture method carried out by the presenter and training by demonstrating the actions that have been conveyed in real life. The results obtained from this activity were that the knowledge and skills of the training participants increased, the increase in the knowledge and skills of the participants was because the participants directly demonstrated the material that had been delivered through the simulation session. In general, this activity can be said to be successful.